Propagation analysis in optical fiber interferometric sensors - Unverdi, N. Ozlem; Turkmen, Oznur (IEEE, 2006)
Optical sensors, one of the principal components of optical communications, are studied, classified and their working principles are explained. The components of optical fiber sensors are discussed and their characteristics evaluated. The Mach-Zehnder interferometric sensor, an optical fiber sensor largely used in physics, chemistry and biomedical applications is assessed, its phase variation analyzed in the light of the Theory of Elasticity, and critical parameters are determined for increasing the sensitivity of the sensor.
Keywords: Computer Science; Engineering; Imaging Science & Photographic Technology